PENGARUH PENGGUNAAN STRATEGI MODELING SIMBOLIK DALAM BIMBINGAN KELOMPOK TERHADAP PEMAHAMAN KARIER SISWA KELAS X SMK AL-ISLAH SURABAYA - Magendra, Lurian (Universitas PGRI Adi Buana Surabaya, 2017)
Abstract The purpose of this research is to find out the influence of using modeling symbolic strategy in group guidance to career understanding of the student 10th class SMK AL ISLAH Surabaya. The research design used one group pretest-posttest design using samples 14 students. The results using technique of modeling symbolic in group guidance with a percentage increase of 30,92%. The conclusion technique of modeling symbolic in guidance group can increase career understanding of student in 10th class SMK AL-Islah Surabaya. Keywords: Modeling Symbolic on group guidance, Career Understanding